Combined PLIF-IR thermal measurements of wavy film flows undergoing forced harmonic excitation - Charogiannis,A; Markides,CN; Mathie,R (2014)
A combined PLIF/IR thermography technique wasdeveloped and employed towards the measurement of unsteadyand conjugate heat transfer in thin, gravity-driven falling liquidfilm flows (with and without flow pulsation) over an inclinedheated metal foil. Simultaneous, local film thickness, film andsubstrate temperature, heat flux exchanged with a heated foiland heat transfer coefficient results are reported for a range ofelectrically applied heat input values, flow Reynolds (Re)numbers and flow pulsation frequencies. Moreover, interfacialwave velocities were calculated from cross-correlations acrosssuccessive thickness profiles. Results concerning theinstantaneous and local heat transfer coefficient variation andhow this is correlated with the instantaneous and local filmthickness variation (waves) suggest that the heat transfercoefficient experiences an enhancement in thinner films. Theparticular observation is most probably attributed to a numberof unsteady flow phenomena within the wavy fluid films thatare not captured by the steady analysis. At low flow Re numbervalues the mean Nusselt (Nu) was around 2.5, in agreementwith laminar flow theory, while at higher Re values, higher Nuwere observed. Finally, lower wave amplitude intensities wereassociated with higher heat transfer coefficient fluctuationintensities.